Ultrahigh-Volumetric-Energy-Density Lithium-Sulfur Batteries with Lean Electrolyte Enabled by Cobalt-Doped MoSe2/Ti3C2Tx MXene Bifunctional Catalyst - Wang, Wei; Huai, Liyuan; Wu, Shangyou; Shan, Jiongwei; Zhu, Junlu; Liu, Zhonggang; Yue, Liguo; Li, Yunyong (ACS nano, 2021)
It is a significant challenge to design a dense high-sulfur-loaded cathode and meanwhile to acquire fast sulfur redox kinetics and suppress the heavy shuttling in the lean electrolyte, thus to acquire a high volumetric energy density without sacrificing gravimetric performance for realistic Li-S batteries (LSBs). Herein, we develop a cation-doping strategy to tailor the electronic structure and catalytic activity of MoSe2 that in situ hybridized with conductive Ti3C2Tx MXene, thus obtaining a Co-MoSe2/MXene bifunctional catalyst as a high-efficient sulfur host. Combining a smart design of the dense sulfur structure, the as-fabricated highly dense S/Co-MoSe2/MXene monolith cathode (density: 1.88 g cm-3, conductivity: 230 S m-1) achieves a high reversible specific capacity of 1454 mAh g-1 and an ultrahigh volumetric energy density of 3659 Wh L-1 at a routine electrolyte and a high areal capacity of ∼8.0 mAh cm-2 under an extremely lean electrolyte of 3.5 μL mgs-1 at 0.1 C. Experimental and DFT theoretical results uncover that introducing Co element into the MoSe2 plane can form a shorter Co-Se bond, impel the Mo 3d band to approach the Fermi level, and provide strong interactions between polysulfides and Co-MoSe2, thereby enhancing its intrinsic electronic conductivity and catalytic activity for fast redox kinetics and uniform Li2S nucleation in a dense high-sulfur-loaded cathode. This deep work provides a good strategy for constructing high-volumetric-energy-density, high-areal-capacity LSBs with lean electrolytes.It is a significant challenge to design a dense high-sulfur-loaded cathode and meanwhile to acquire fast sulfur redox kinetics and suppress the heavy shuttling in the lean electrolyte, thus to acquire a high volumetric energy density without sacrificing gravimetric performance for realistic Li-S batteries (LSBs). Herein, we develop a cation-doping strategy to tailor the electronic structure and catalytic activity of MoSe2 that in situ hybridized with conductive Ti3C2Tx MXene, thus obtaining a Co-MoSe2/MXene bifunctional catalyst as a high-efficient sulfur host. Combining a smart design of the dense sulfur structure, the as-fabricated highly dense S/Co-MoSe2/MXene monolith cathode (density: 1.88 g cm-3, conductivity: 230 S m-1) achieves a high reversible specific capacity of 1454 mAh g-1 and an ultrahigh volumetric energy density of 3659 Wh L-1 at a routine electrolyte and a high areal capacity of ∼8.0 mAh cm-2 under an extremely lean electrolyte of 3.5 μL mgs-1 at 0.1 C. Experimental and DFT theoretical results uncover that introducing Co element into the MoSe2 plane can form a shorter Co-Se bond, impel the Mo 3d band to approach the Fermi level, and provide strong interactions between polysulfides and Co-MoSe2, thereby enhancing its intrinsic electronic conductivity and catalytic activity for fast redox kinetics and uniform Li2S nucleation in a dense high-sulfur-loaded cathode. This deep work provides a good strategy for constructing high-volumetric-energy-density, high-areal-capacity LSBs with lean electrolytes.